“You Call that Meat?” Investigating Social Media Conversations and Influencers Surrounding Cultured Meat - Annie R. Specht; Joy N Rumble; Emily B. Buck (Journal of Applied Communications, 2020)
Cultured meat has yet to reach store shelves but is nonetheless a growing issue for consumers, producers, and government regulators, many of whom have taken to social media to discuss it. Using a conceptual framework of social cognitive theory and issues management, this qualitative content analysis investigated social-media discourse surrounding the topic of cultured meat in the United States by describing the content of the discussion in late 2018 and identifying individual influencers and communities of influencers engaged in the discussion. Data were collected from Twitter using listening platform Sysomos MAP. The thematic analysis revealed eight themes: legality and marketing, sustainability, acceptance, business, animal concerns, science and technology, health concerns, and timeline, and indicated that conflicting views and questions about cultured meat exist among conversation participants. Top influencers included philanthropists, government officials, journalists and writers, and animal-welfare advocates. These influencers were grouped into four distinct communities based on interactions with each other and other users. The topics identified in the analysis provide insight into ways in which communicators can enter these conversations, and influencer communities represent groups of users whose broad reach could more easily transmit pro-agriculture messages.
Keywords: Cultured meat; social cognitive theory; issues management; social media